3D Linked Subduction, Dynamic Rupture, Tsunami, and Inundation Modeling: Dynamic Effects of Supershear and Tsunami Earthquakes, Hypocenter Location, and Shallow Fault Slip - Aniko Wirp, Sara; Gabriel, Alice-Agnes; Schmeller, Maximilian; H. Madden, Elizabeth; van Zelst, Iris; Krenz, Lukas; van Dinther, Ylona; Rannabauer, Leonhard (Frontiers in Earth Science, 2021)
Physics-based dynamic rupture models capture the variability of earthquake slip in space and time and can account for the structural complexity inherent to subduction zones. Here we link tsunami generation, propagation, and coastal inundation with 3D earthquake dynamic rupture (DR) models initialized using a 2D seismo-thermo-mechanical geodynamic (SC) model simulating both subduction dynamics and seismic cycles. We analyze a total of 15 subduction-initialized 3D dynamic rupture-tsunami scenarios in which the tsunami source arises from the time-dependent co-seismic seafloor displacements with flat bathymetry and inundation on a linearly sloping beach. We first vary the location of the hypocenter to generate 12 distinct unilateral and bilateral propagating earthquake scenarios. Large-scale fault topography (and the associated rheological complexity) leads to localized up- or downdip propagating supershear rupture depending on hypocentral depth. Albeit dynamic earthquake differences (rupture speed, peak slip-rate, fault slip, bimaterial effects), the effects of hypocentral depth (25 to 40~km, all consistent with the SC model) on tsunami dynamics are negligible. Lateral hypocenter variations lead to small effects such as delayed wave arrival of up to 80~s and differences in tsunami amplitude of up to 0.5~m at the coast. We next analyse inundation on a coastline with complex topo-bathymetry which increases tsunami wave amplitudes up to $≈$1.5~m compared to a linearly sloping beach. Motivated by structural heterogeneity in subduction zones, we analyse a scenario with increased Poisson's ratio of $ν=0.3$ which results in close to double the amount of shallow fault slip, $≈$1.5~m higher vertical seafloor displacement, and a difference of up to $≈$0.6~m in coastal tsunami amplitudes. Lastly, we model a ``tsunami earthquake'' with low rupture velocity and peak slip rates and twice as high tsunami potential energy. We triple fracture energy which again doubles the amount of shallow fault slip, but also causes a 2~m higher vertical seafloor uplift and the highest coastal tsunami amplitude ($≈$8~m) and inundation area compared to all other scenarios. Our sensitivity analysis for a generic megathrust setting can provide building blocks towards dynamic rupture modeling complementing Probabilistic Tsunami Hazard Analysis.